Water security in Mbagathi and Stony Athi catchments within Kenya’s SGR corridor under environmental and socio-economic change - Catherine C. Sang; Daniel O. Olago (Discover Water)
Abstract Water insecurity, driven by urbanization, population growth, land use and climate change, poses a global challenge. This study examines water supply and demand trends in the Mbagathi-Stony Athi sub-catchments, highlighting urbanization's impact in a semi-arid context. Using GIS, and the WEAP model, various scenarios were simulated. Results show annual rainfall increased insignificantly (p = 0.61) from 1981 to 2019. By 2063, rainfall is projected to rise by 12.43% (RCP 4.5) and 21.02% (RCP 8.5). Mean temperature increased by 0.88 °C (1981–2019) and is projected to rise by 1.70 °C (RCP 4.5) and 1.75 °C (RCP 8.5) by 2063. Land use analysis (2000–2019) showed a 53.67% increase in built-up areas and a 99.32% decline in wetlands. Between 2000 and 2019, the annual supply, demand, and unmet demand increased by 171.64%, 147.56%, and 73%, respectively. Land use changes between 2000 and 2019, particularly the increase in shrublands and decline in bare land, contributed to a 25.51% decrease in surface runoff and a 3.55% rise in total annual evapotranspiration. Future projections indicate surface runoff decreases of up to 4.47% under RCP 4.5 and increases of 9.38% under RCP 8.5. Potential evapotranspiration is projected to rise by 23.39% (reference), 16.44% (RCP 4.5), and 11.19% (RCP 8.5). Water demand will increase across all scenarios, peaking at 184% under high urbanization, while unmet demand will rise by up to 162.47% under irrigation expansion. Water scarcity is expected to worsen due to climate change, population growth, and land use shifts. These findings inform sustainable water resource management in development corridors.